Agent-Based Cloud Resource Management for Secure Cloud Infrastructures - Balogh, Zoltán; Gatial, Emil; Hluchý, Ladislav; Toegl, Ronald; Pirker, Martin; Hein, Daniel (Computing and Informatics, 2015)
The cloud offers clear benefits for computations as well as for storage for diverse application areas. Security concerns are by far the greatest barriers to the wider uptake of cloud computing, particularly for privacy-sensitive applications. The aim of this article is to propose an approach for establishing trust between users and providers of cloud infrastructures (IaaS model) based on certified trusted agents. Such approach would remove barriers that prevent security sensitive applications being moved to the cloud. The core technology encompasses a secure agent platform for providing the execution environment for agents and the secure attested software base which ensures the integrity of the host platform. In this article we describe the motivation, concept, design and initial implementation of these technologies.